Infection in preterm infants receiving topical emollient oil massage: a systematic review and meta-analysis of randomised control trials - Natnael Moges; Zemen Mengesha; Zebenay Workneh Bitew; Fekadeselassie Belege Getaneh; Aden Asmare; Bezabih Abayneh; Endalk Birre; Anissa Mohammed; Amare Muche; Alemu Gedefie; Yibeltal Asmamaw; Dires Mihretie Birhanu; et al. (BMJ Publishing Group, 2024)
Background Preterm infants are highly susceptible to infections, which significantly contribute to morbidity and mortality. This systematic review and meta-analysis investigated the effectiveness of topical emollient oil application in preventing infections among preterm infants.Methods A comprehensive search was conducted across multiple electronic databases (PubMed, Cochrane, Scopus, Clinical trials, Epistemonikos, HINARI and Global Index Medicus) and other sources. A total of 2185 articles were identified and screened for eligibility. The quality of included studies was assessed using the Cochrane Risk of Bias Tool for randomised controlled trials. Data analysis was performed using StataCrop MP V.17 software. Heterogeneity among the studies was evaluated using the I2 and Cochrane Q test statistics. Sensitivity and subgroup analyses were conducted. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist guided the presentation of the results.Results Of 2185 retrieved articles from initial searches, 11 met eligibility criteria and were included in the final analysis. A random effects meta-analysis revealed that infants who received massages with emollient oils had a 21% reduced risk of infection (risk ratio=0.79, 95% CI 0.64 to 0.97, I2=0.00%). Subgroup analyses indicated that preterm babies who received topical emollient oil massages with coconut oil, administered twice a day for more than 2 weeks, had a lower likelihood of acquiring an infection compared with their non-massaged counterparts.Conclusion It is quite evident from this analysis that topical emollient oil application in preterm neonates is most likely effective in preventing infection. However, further studies, particularly from the African continent, are warranted to support universal recommendations.